Excitability in the H2+O2 reaction on a Rh(110) surface induced by high coverages of coadsorbed potassium - Rafti, Matías (2014)
By means of photoemission electron microscopy as spatially resolving method, the effect of high coverages of coadsorbed potassium (0.16 ≤ θK ≤ 0.21) on the dynamical behavior of the H2 + O2 reaction over a Rh(110) surface was investigated. We observe that the originally bistable system is transformed into an excitable system as evidenced by the formation of target patterns and spiral waves. At K coverages close to saturation (θK ≈ 0.21) mass transport of potassium with pulses is seen.